The generalized viscosity explicit rules for solving variational inclusion problems in Banach spaces. (2nd December 2021) - Cholamjiak, Prasit; Pholasa, Nattawut; Suantai, Suthep; Sunthrayuth, Pongsakorn
Abstract : In this paper, we propose a generalized viscosity explicit method for finding zeros of the sum of two accretive operators in the framework of Banach spaces. The strong convergence theorem of such method is proved under some suitable assumption on the parameters. As applications, we apply our main result to the variational inequality problem, the convex minimization problem and the split feasibility problem. The numerical experiments to illustrate the behaviour of the proposed method including compare it with other methods are also presented.